Alien honeybees increase pollination risks for range‐restricted plants. Issue 5 (28th January 2018) - Norfolk, Olivia; Gilbert, Francis; Eichhorn, Markus P.
Abstract: Aim: Range‐restricted species are of high conservation concern, and the way in which they interact with more widespread species has implications for their persistence. Here, we determine how the specialization of mutualistic interactions varies with respect to the geographic range size of plants and pollinators and assess how they respond to the introduction of the alien honeybee. We also compare network characteristics (connectance, specialization and nestedness) between an invaded low mountain and non‐invaded high mountain network. Location: St Katherine Protectorate, South Sinai, Egypt. Methods: We quantified bee–plant interactions in 42 plots between April and July 2013 and created visitation networks for the low mountains (beehives present) and the high mountains (beehives absent). We then compared visitation network metrics between range‐restricted, regionally distributed and widespread plants and pollinators and assessed topological differences between the low and high mountain networks. Results: Range‐restricted bees were involved in a significantly higher number of total interactions than regional and widespread native bees, but showed no evidence of increased generalization. In contrast, range‐restricted plants were involved in fewer interactions and exhibited significantly higher specialization and a high dependency on range‐restricted pollinators. The introduced honeybee acted as a super‐generalist and was associated with an increase in network‐level generalization and nestedness. Honeybees exhibited high levels of resource overlap with range‐restricted bees and made few visits to range‐restricted plant species. Main conclusions: Range‐restricted plants are more specialized in their interactions than range‐restricted pollinators, suggesting that the forces shaping the structure of interaction network can vary between partners. Alien honeybees made few visits to range‐restricted plants, but exhibited disproportionately high levels of floral competition with range‐restricted bees. If high levels of competition lead to population declines then specialized range‐restricted plants will be at higher risk of pollen deficits than more widespread species.